2022
DOI: 10.3390/biomedicines10102348
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Released by Corneal Stromal Cells Show Molecular Alterations in Keratoconus Patients and Induce Different Cellular Behavior

Abstract: Exosomes have been related to various disorders, but their study in relation to ocular pathologies has been limited. In this article, we analyze exosomes produced by corneal stromal cells from healthy individuals and from patients with keratoconus. The proteomic study allowed for the identification of 14 new proteins with altered expression, related to molecules previously associated with the pathology. miRNA analysis detected 16 altered species, including miR-184, responsible for familial severe keratoconus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The exosome suspension was applied to a standard SDS-PAGE gel and allowed to penetrate 1 cm into the resolving gel. The protein mixture was stained with Coomassie, extracted, and cut into 1 mm 2 fragments, which were deposited in 96-well plates and processed in a Proteineer DP (Bruker Daltonics, Bremen, Germany), using a digestion protocol based on Schevchenko et al [54] with minor variations as previously described [55]. The finally obtained tryptic-eluted peptides were dried by fast vacuum centrifugation.…”
Section: Proteomic Analysismentioning
confidence: 99%
“…The exosome suspension was applied to a standard SDS-PAGE gel and allowed to penetrate 1 cm into the resolving gel. The protein mixture was stained with Coomassie, extracted, and cut into 1 mm 2 fragments, which were deposited in 96-well plates and processed in a Proteineer DP (Bruker Daltonics, Bremen, Germany), using a digestion protocol based on Schevchenko et al [54] with minor variations as previously described [55]. The finally obtained tryptic-eluted peptides were dried by fast vacuum centrifugation.…”
Section: Proteomic Analysismentioning
confidence: 99%
“…This study also found upregulated expression of corneal epithelial miR-1207 in response to bacterial antigens, suggesting miR-1207’s involvement in host defense mechanisms. miR-4466 was found to be overexpressed in human corneal stromal cell exosomes of patients with keratoconus compared to healthy controls [ 89 ]. This upregulation was also detected in the tears from VKC patients and may indicate miR-4466’s potential involvement in corneal surface integrity.…”
Section: Vernal Keratoconjunctivitismentioning
confidence: 99%
“…A progressive and degradative disorder, KC presents as irregular astigmatism, myopia, and corneal scarring, which worsen over time and can result in vision loss [3]. At the tissue level, KC is marked by centralized thinning of the stroma, breaks in Bowman's layer, compaction of the collagen fibers in the stroma, and iron deposition in the epithelial basement membrane [1,[4][5][6][7]. All five layers of the cornea may be affected by KC pathogenesis, but the characteristics mentioned are well-recognized markers of KC [1].…”
Section: Introductionmentioning
confidence: 99%